Aplikasi Dosis Pupuk NPK Majemuk terhadap Pertumbuhan dan Hasil Tanaman Semangka pada Lahan Rawa Lebak - Muhammad Rizqillah Hidayat (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2013)
Watermelon come from arid tropical and subtropical regions of Africa. Watermelon is an annual plant that grows and requires full sun. Lebak swamp soil is known to have the properties and properties of acid sulphate soils that affect the physical, chemical and biological properties of the soil. Fertilizers are the key to soil fertility. Compound fertilizer is a fertilizer that contains several nutrients, for example nutrients (nitrogen), potassium (K) and phosphorus (P). This study aims (i) to obtain influence and (ii) the best dosage of various applications of NPK Compound fertilizer dosage on the growth and yield of watermelon plants on lebak wetland. The study was conducted in Teluk Buluh Village, Banjang District, Hulu Sungai Utara Regency in July - September 2013, this study used a single randomized block design (RBD) with 5 treatments and 5 replications so that there were 25 experimental units. The factors tested were various doses of Compound NPK fertilizer, namely m1: 0.333 t.ha-1 (200 g / bed), m2: 0.666 t.ha-1 (400 g / bed), m3: 0.999 t.ha-1 ( 600 g / bed), m4: 1,332 t.ha-1 (800 g / bed) and m5: 1,665 t.ha-1 (1000 g / bed). The results of this study indicate that the dosage of Compound NPK fertilizer given to watermelon plants in swampland area had a significant effect on plant length and number of leaves aged 25 HST and 30 HST and had a very significant effect on the fruit weight and number of watermelon plants with the best treatment is m3: 0.999 t.ha-1 (600 g / bed).